DESIGNING INCLUSIVE LANGUAGE ASSESSMENTS FOR LEARNERS WITH SPECIAL EDUCATIONAL NEEDS - Aktamova Zarnigor Yahyo qizi; Khonsaidova Maktuba Makhamadalievna (TADQIQOTLAR, 2026)
This article explores principles and practical strategies for designing accessible and equitable language assessments. It highlights differentiated assessment formats, the use of assistive technologies, flexible timing, multimodal input/output options, and simplified language without reducing academic rigor. The discussion emphasizes that inclusive assessment is not about lowering standards but about providing equitable pathways  for  all  learners  to  demonstrate  their  abilities.  Ultimately,  inclusive assessment  design  contributes  to  more  accurate  evaluation,  improved  learner motivation, and greater educational equity.